EP827 Pathologic findings in risk-reducing salpingo-oophorectomy (RRSO) in women with BRCA1 or BRCA2 mutations: a single center experience. (1st November 2019) - De Leo, A; Ceccarelli, C; Turchetti, D; Santini, D; Perrone, AM; De Iaco, P
Abstract : Introduction/Background: Bilateral salpingo-oophorectomy offers the greatest risk reduction for ovarian cancer in high-risk women with an identified BRCA germline mutation. The aim of this study was to define the incidence of precursor lesions and cancer after RRSO. Methodology: We retrospectively reviewed 71 BRCA-mutated patients who underwent RRSO from 2012 to 2017. All cases were examined according to the protocol for Sectioning and Extensively Examining the FIMbriated End (SEE-FIM). Results: The median age at RRSO was 49.9 years. BRCA 1 mutation was detected in 46/71 (64.8%) patients, BRCA2 mutation in 25/71 (35.2%) patients. 50/71 (70.4%) patients had breast cancer. BRCA1 breast cancer was more frequently high grade (G3) and showed a strong association to triple negative phenotype (p=0.001), high TILs (tumor-infiltrating lymphocytes), and aberrant expression of p53 (p=0.01). Occult invasive gynecological cancer was detected in two patients: a tubal high grade serous carcinoma in a BRCA2+ patient and an ovarian low-grade endometrioid carcinoma in a BRCA1+ patient. 5 (7%) STIC (Serous Tubal Intraepithelial Carcinoma), 5 (7%) STIL (Serous Tubal Intraepithelial Lesion) and 13 (18.3%) SCOUT (Secretory Cell Outgrowth) were detected. 10 patients had endometriosis and benign ovarian lesions were found in 17 cases. The detection rate of STIC/STIL or invasive cancer was 16.9% (12/71). Tubal lesions were more common in BRCA2 mutation carriers (68% vs. 39%). Conclusion: In our institution, a rigorous surgical protocol with meticulous pathologic review at RRSO yielded an overall detection rate of 9.8% for occult gynecological carcinoma in BRCA mutation carriers. Disclosure: Nothing to disclose.